IMPLEMENTASI PROJECT-BASED LEARNING (PJBL) BERBASIS KEARIFAN LOKAL TARI OREK-OREK DALAM MENGUATKAN PROFIL PELAJAR PANCASILA PADA SISWA SD - Diaz Fernanda, Alfina Mutiara; Dewi Pramesta, Aulia Luthfi; Zakiyah, Yumi; Narimo, Sabar; Sumardjoko, Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the application of Project-Based Learning (PjBL) based on the local wisdom of Orek-Orek dance as a strategy to strengthen the Pancasila Student Profile in fifth-grade students at SDN Wonokerto 1 Ngawi. This learning model was developed by integrating local cultural elements into the learning process so that students gain experiences that not only emphasize academic aspects but also strengthen character in accordance with the requirements of the Merdeka Curriculum. The research used a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, documentation, and performance assessments to obtain a comprehensive picture of the learning process and outcomes. The results of the study show that the application of PjBL based on Orek-Orek dance was able to create an authentic and meaningful learning experience through cultural exploration, group collaboration, project planning, practice, and performance. This process contributed to an increase in students' cooperation, creativity, communication, independence, problem-solving, and understanding of regional cultural values. In addition, improvements were seen in all dimensions of the Pancasila Student Profile through a comparison of initial and final assessments, covering the aspects of faith and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity. These findings confirm that PjBL integrated with local wisdom can be an effective and relevant learning strategy.